Living on the edge transgression, exclusion, and persecution in the Middle Ages - Nieto-Isabel, Delfi I.; Miquel Milian, Laura (Studies in medieval and early modern culture, 2022)
Intro -- Acknowledgements -- Table of Contents -- Foreword -- Introduction All but Marginal: The Co-Constructions of Otherness in the Middle Ages -- Part I: The Fundamental Edge -- Chapter 1 Reading in Community, Writing a Community: Douceline's Vida and the Beguines of Roubaud -- Chapter 2 "No More Horrified by Them": Royal Holy Women and Lepers in Twelfth- and Thirteenth-Century Hagiography -- Chapter 3 Exclusion and Marginalization of Widows in Late Medieval Barcelona -- Chapter 4 Ageing Women, (In)Visible Bodies: Iconographies on the Edge in Late-Medieval Iberia (Thirteenth to Fifteenth Centuries) -- Part II: The Religious Edge -- Chapter 5 Catharistae in Question: A Case of Rupture in the Manichaean Sect -- Chapter 6 Art, Iconography, and Orthodoxy between the Fourth and Fifth Centuries: The Case of the Ascension -- Chapter 7 The Early Cistercian Order and the Persecution of Heresy: Bernard of Clairvaux's and Geoffrey of Auxerre's Attitudes Towards the Violent Persecution of Heretics -- Chapter 8 From Persecution to Exile: Jewish Views on Christians and Christianity in the Late Medieval Crown of Aragon -- Part III: The Edge of Society -- Chapter 9 Social Domination and Resistance: Slavery in the Medieval Christian Western Mediterranean -- Chapter 10 Diverging Views of the "Leper" in Legal, Literary, and Doctrinal Texts from Thirteenth-Century Western Europe -- Chapter 11 On the Margins of Society: Exclusion through Exile as a Structuring Motif in Sir Orfeo -- Chapter 12 Defying Containment: The Use of the Frame in Depictions of Monstrous Peoples in Monte Cassino Rhabanus Maurus Codex -- Notes on Contributors -- Index.